2004
DOI: 10.1002/rcm.1587
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous selected reaction monitoring, MS/MS and MS3 quantitation for the analysis of pharmaceutical compounds in human plasma using chip‐based infusion

Abstract: An assay method with mass spectrometric detection was developed for the quantitative analysis of a pharmaceutical compound and its major metabolite in human plasma using chip-based infusion. Liquid-liquid extraction sample preparation was found to be essential to minimize matrix suppression and to achieve a limit of quantitation (LOQ) of 2.5 ng/mL using a 100 microL plasma aliquot. The potential for simultaneous quantitation in selected reaction monitoring (SRM), tandem mass spectrometry (MS/MS) (enhanced prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…This is particularly a concern for drugs which generate phase II metabolites. Nevertheless, the quantitation of pharmaceutical compounds in biological matrices without chromatographic separation using chip-based infusion has been successfully demonstrated [20,21]. With LC or infusion systems, cycle times below 10-20 s may be challenging to achieve on a routine base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly a concern for drugs which generate phase II metabolites. Nevertheless, the quantitation of pharmaceutical compounds in biological matrices without chromatographic separation using chip-based infusion has been successfully demonstrated [20,21]. With LC or infusion systems, cycle times below 10-20 s may be challenging to achieve on a routine base.…”
Section: Resultsmentioning
confidence: 99%
“…To really benefit from MALDI-SRM/MS approaches without chromatography the metabolism of the drug needs to be well characterized. A strategy to improve the selectivity of chip-based infusion assay was proposed by Leuthold et al [21] where the authors calculated a ratio between the SRM and MS 3 results. A similar set-up could also be used with the present MALDI-SRM/MS assay to check the selectivity of the analysis.…”
Section: Samplementioning
confidence: 99%
“…ESI-MS under nanospray conditions at sub L/min flow rates may lead to more uniform response factors. Chipbased nanoelectrospray systems [45][46][47] are another tool to reduce matrix effects and improve sensitivity [48]. APCI [49] and APPI [50] are widely used in the pharmaceutical industry, yet they are not frequently used for metabomonics investigations.…”
Section: Ms Ionization Techniques and Analyzersmentioning
confidence: 99%
“…Very few authors reported the use of MS 3 on a hybrid quadrupole-linear ion trap mass spectrometer for the quantitative analysis of drugs in biological fluids [20,21] and, to the best of our knowledge, this appears to be the first complete validation of a quantitative method using LC-MS 3 . Herein we described, for the first time the validation of a quantitative method using fully automated protein precipitation, fast liquid chromatography and MS 3 as scan function by using a hybrid quadrupole-linear ion trap mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%